Avaliação das exposições dos envolvidos em procedimentos Intervencionistas usando método Monte Carlo (Brazilian Journal of Radiation Sciences, 2017)
This study presents a computational model of exposure of a patient, cardiologist and a nurse in a typical scenario of cardiac interventional procedures. In this case, a set of conversion coefficients (CC) for effective dose (E) in terms of the kerma-area product (KAP) was calculated for the individuals involved, using seven different energy spectra and eight beam projections. We also calculated the CC for the skin entrance dose (ESD) of the patient normalized by PKA. All individuals were represented by anthropomorphic computer simulators embedded in a radiation transport code based on Monte Carlo simulation.